2006
DOI: 10.1001/archinte.166.13.1350
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Transesophageal Echocardiography, Helical Computed Tomography, and Magnetic Resonance Imaging for Suspected Thoracic Aortic Dissection

Abstract: All 3 imaging techniques, ie, TEE, helical CT, and MRI, yield clinically equally reliable diagnostic values for confirming or ruling out thoracic aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
190
1
20

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(212 citation statements)
references
References 28 publications
1
190
1
20
Order By: Relevance
“…Reports of newer-generation multidetector helical CT scanners show sensitivities of up to 100% and specificities of 98% to 99%. [29][30][31][32] The sequence for a CT performed in the potential setting of acute AoD generally would include a noncontrast study to detect subtle changes of IMH, followed by a contrast study to delineate the presence and extent of the dissection flap, identify regions of potential malperfusion, and demonstrate contrast leak indicating rupture. Imaging of the vascular tree from the thoracic inlet to the pelvis, including the iliac and femoral arteries, provides sufficient information to plan surgical or endovascular treatment, if needed.…”
Section: Computed Tomographic Imagingmentioning
confidence: 99%
“…Reports of newer-generation multidetector helical CT scanners show sensitivities of up to 100% and specificities of 98% to 99%. [29][30][31][32] The sequence for a CT performed in the potential setting of acute AoD generally would include a noncontrast study to detect subtle changes of IMH, followed by a contrast study to delineate the presence and extent of the dissection flap, identify regions of potential malperfusion, and demonstrate contrast leak indicating rupture. Imaging of the vascular tree from the thoracic inlet to the pelvis, including the iliac and femoral arteries, provides sufficient information to plan surgical or endovascular treatment, if needed.…”
Section: Computed Tomographic Imagingmentioning
confidence: 99%
“…Computed tomography has been a widely used imaging technique for diagnosing aortic dissection, as the diagnostic accuracy was excellent (pooled sensitivity, 100%; pooled specificity, 98%) 6. Sometimes an intimal flap or tear at the proximal ascending aorta is not shown on enhanced CT, as in our case 3.…”
Section: Discussionmentioning
confidence: 68%
“…More recently, however, it has been shown that aortic dissection is diagnosed with equivalent reliability in a number of imaging modalities including echocardiography and computed tomography (Litmanovich et. al, 2009;Shiga et. al, 2006).…”
Section: Aortic Dissectionmentioning
confidence: 98%